Kajian Penggunaan Abah-Abah Terhadap Keselamatan Pekerja di Bangunan Bertingkat - Shafii, Haryati; Hawae, Syahira; Md Yassin, Azlina; Masram, Haidaliza; kHALID, ZAILAWATI; Sarpin, Norliana (Research in Management of Technology and Business, 2025)
This study focuses on the issue of improper use and management of safety harnesses, which do not comply with safe equipment usage procedures and may lead to accidents at construction sites. The objectives of this study are: (i) to examine the key factors contributing to safety harness-related accidents among workers in high-rise buildings, and (ii) to propose measures to reduce such accidents among workers in high-rise construction. A qualitative approach was employed, involving interviews with selected informants from Class G7 contractors. Site Managers and Safety and Health Managers were interviewed, and the transcripts were analyzed using thematic analysis. The findings reveal that informants agree that the main factors contributing to safety harness-related accidents in high-rise buildings include worker-related issues, employer responsibility, safety training, and equipment condition. As for the proposed measures to reduce these accidents, the study found that the majority of informants emphasized the importance of workers actively participating in safety programs or training organized by their companies. Employers were also urged to enforce stricter safety rules and procedures at construction sites. It is hoped that this study will help address the rising concern of safety harness-related accidents at construction sites.